Surfactant Utilization In Oil Sludge Biode Gradation Using Slurry Bioreactor - Syafrizal Syafrizal; Devitra Saka Rani; Yanni Kussuryani (Testing Center for Oil and Gas LEMIGAS, 2009)
Oil sludge from petroleum industry effluent is classified as hazardous waste and requiredspecial treatment before discharge to the environment. Biodegradation using bacterialactivities is a general treatment for oil sludge processing. However, the bacterial abilityin oil sludge biodegradation is blocked by non-aqueous phase liquid of oil sludge. Twopossible ways of enhancing the bioavailability of oil sludge are surfactants application and slurry bioreactors system. The objective of this study is to obtain the surfactant which can increase oil sludge biodegradation using simple slurry bioreactor. The surfactant selection obtained Emulsogen LP (58% effectiveness) which was examined based on HLB value, nonionic character, and surfactant effectiveness. Emulsogen LP is readily biodegradable which reached 93% biodegradability in 15 days. The biodegradation test showed that Emulsogen LP addition on its Critical Micelle Concentration (10 mg/L) enhanced oil sludge biodegradation in 3 bacterial cultures of Pseudomonas aeruginosa, Bacillus subtilis, and Actinobacter baumanni after 48 hours. By surfactant addition, oil sludge biodegradation reached 37-49% whereas without surfactant addition it only reached 28-33%. The highest oil sludge biodegradation was obtained in P. aeruginosa cultures with Emulsogen LP addition (49%). The surfactant addition had no effect on microbial growth. Moreover, P. aeruginosa population was increased by surfactant addition.